A Deprotection‐free Method for High‐yield Synthesis of Graphdiyne Powder with In Situ Formed CuO Nanoparticles. (7th September 2022) - Li, Jian; Han, Xu; Wang, Dongmei; Zhu, Lei; Ha‐Thi, Minh‐Huong; Pino, Thomas; Arbiol, Jordi; Wu, Li‐Zhu; Nawfal Ghazzal, Mohamed
Abstract: With a direct band gap, superior charge carrier mobility, and uniformly distributed pores, graphdiyne (GDY) has stimulated tremendous interest from the scientific community. However, its broad application is greatly limited by the complicated multistep synthesis process including complex deprotection of hexakis‐[(trimethylsilyl)ethynyl]benzene (HEB‐TMS) and peeling of GDY from the substrates. Here, we describe a deprotection‐free strategy to prepare GDY powder by directly using HEB‐TMS as the monomer. When CuCl was used as the catalysts in DMF solvent, the yield of GDY powder reached ≈100 %. More interestingly, uniformly dispersed CuO nanoparticles with an average diameter of ≈2.9 nm were in situ formed on GDY after the reaction. The prepared CuO/GDY was demonstrated an excellent co‐catalyst for photocatalytic hydrogen evolution, comparable to the state‐of‐art Pt co‐catalyst. The deprotection‐free approach will widen the use of GDY and facilitate its scaling up to industrial level. Abstract : A deprotection‐free method was developed for the synthesis of GDY powder with 100 % yield. CuO nanoparticles with an average diameter of ≈2.9 nm were in situ generated on GDY after the reaction. The as‐prepared CuO/GDY was an excellent co‐catalyst for photocatalytic hydrogen evolution, comparable to the start‐of‐art Pt cocatalyst. This work provides a straightforward deprotection‐free approach, which will definitely expand the diverse applications of GDY.